O uso do Teorema da Função Implícita no dimensionamento de redes neurais multi-camadas - Belonsi, Marcelo Henrique (1996)
This work presents a method for dimensioning artificial neural networks with a single hidden layer, considering the trainability conditions and the approximation accuracy. The functional approximation accuracy is highly dependent on the network structure. Therefore, to guarantee a reasonable approximation, a method is presented to determine the number of elements in the hidden layer, using the implicit function theorem. Some simulations illustrates the theoretical results obtained in this work.